OTHERED AND EXILED: NAVIGATING THE IN-BETWEEN IN THE RELUCTANT FUNDAMENTALIST - Gangan, Nisha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the thematic intersections of identity, belonging, and alienation in Mohsin Hamid’s The Reluctant Fundamentalist, situating the protagonist, Changez, within the broader socio-political landscape of post-9/11 America. Through a critical analysis of Changez’s trajectory from an aspiring immigrant embodying the ideals of the American Dream to a disillusioned critic disavowing its tenets. this paper interrogates the processes of systemic othering and cultural exclusion exacerbated by the post-9/11 "War on Terror." The research recontextualises the concept of "fundamentalism," moving beyond its conventional association with religious extremism to encompass ideological and economic rigidities intrinsic to late capitalism and Western imperial hegemony. The study reveals the enduring impact of cultural alienation and identity fragmentation by foregrounding Changez’s navigation of liminal spaces between his Pakistani heritage and American aspirations. This paper argues that Hamids narrative functions as a critique of the fragility of multiculturalism and a cautionary reflection on the global implications of exclusionary policies and attitudes. Ultimately, the analysis contributes to discourses on identity politics, transnationalism, and the ethics of coexistence in a polarised global order.